Evaluation of slaughterhouse pig ovaries and recovery of Cumulus-Oocyte-Complexes (COCs) - Ong, Debra Hsiang Shiang (Universiti Malaysia Sabah, 2018)
Pig production is important in Malaysia as 40 % of Malaysian eat pork. As population increases, the demand of pork also increases. However, the pig production in Malaysia has shown a slightly decreasing trend. To boost up the production, in vitro embryo production (IVEP) is used. However, there is lack of information on IVEP for porcine in Malaysia. Therefore, the objectives of this study are to determine the relationship between ovarian types, quality of slaughterhouse pig ovaries and the recovery rate and quality of recovered COCs. This research was conducted at Plant Physiology Laboratory, Faculty of Sustainable Agriculture, Universiti Malaysia Sabah, Sandakan campus from May 2017 until July 2017 to evaluate the slaughterhouse pig ovaries and recovery of the cumulus-oocyte-complexes (COCs) from the ovaries. The pig ovaries were collected from local pig slaughterhouse and marked left and right. The ovaries were grouped into ovary with corpus luteum (CL+) and without corpus luteum (CL-). Evaluations based on weight of ovaries and number of visible follicles were done in the laboratory. The COCs were aspirated with 25G needle attached to a 10 ml syringe. Aspirated materials were observed under light microscope with magnification of XlOO and X400 graded into 4 grades: (a) Grade A: oocyte homogenously surrounded by cumulus cells; (b) Grade B: oocyte partially surrounded by cumulus cells; (c) Grade c: Oocyte not surrounded by cumulus cells; (d) Grade D: degeneration appeared both in oocyte and cumulus cells. Grade A and Grade B were considered as normal COCs, while Grade C and D were graded as abnormal COCs. The number of follicles and COCs for each grade were analysed by using mean ± SE and also inserted into t-test to identify variations between groups. The recorded percentages of ovaries that had been retrieved from slaughterhouse was 3.57% (six) CL+ ovaries and 96.43% (162) CL-ovaries. The number of surface follicles was found comparatively (P>0.05) higher in left ovary (82.75±3.56) than right ovary (79.25±3.15). The number of normal COCs (Grade A and Grade B) found comparatively (P>0.05) higher in left ovary (6.74±0.57 and 5.35±0.42 respectively) than right ovary (6.23±0.52 and 5.20±0.35 respectively). There was no significant different between weight of left ovary and right ovary. When ovaries compared between CL+ and CL-, CL+ ovary (3.42g±0.64g) was significantly (P<0.05) heavier than CL-ovary (2.67g±0.07g). The number of abnormal COCs in CL+ ovary (6.50±1.12) was significantly higher (P<0.05) than CL-ovary (6.40±0.41). Number of surface follicles and number of normal COCs also significant higher (P<0.05) in CL-ovaries than CL+ ovaries. From the experiment, it is found that COCs retrieved from left and right ovaries had no significant differences and CL-ovaries contributed better quality of COCs. Therefore, the finding suggested that the any position of ovary without corpus luteum might be suitable to obtain good quality COCs for in vitro embryo production (IVEP).